Disposable Diaper Impact The Toddler’s Toilet Training Readiness - Yuni Sufyanti Arief; Nuzul Qur'aniati; Wahyuning Hidayati (Jurnal Ners, 2009)
Introduction : Toilet training is an important developmental milestone in every child’s life. The children who wear cloth diapers than disposable diaper are out of diaper 12 months earlier because they can feel the wetness when they urinate. Kinds of underwear may facilitate the development of toileting skill. The objective of this study was to learn differentiation about toilet training practised between the toddler who ever wear disposable diaper and the toddler who never wear disposable diaper.Methods : This study used case control design. Population was consist of 45 toddler in 24-36 month old. The samples were 34 respondents, 21 toddler as 1st group  who ever wear disposable diaper and 13 toddler as 2nd group who never one, taken according to inclusion criteria. The independent variables were wear disposable diaper and never one. The dependent variable was toilet training practised such as the toileting skill of toddler, method of toilet training by the parent, toddler readiness to start toilet training and the parents and environment readiness to start toilet training for toddler. Data were taken by using questionnaire and analysed using Mann Whitney test with significance level of  α<0.05.Results : The result showed that there was no differentiation about the toileting skill of toddler (p=0.631), method of toilet training (p=0.249), and the parents and environment readiness to start toilet training (p=0.207) between the groups. There was differentiation about the toddler readiness to start toilet training between the groups with significance level p=0.000.Conclusion : It can be concluded that there are no differentiation about the toilet training practiced beetwen the groups. Discussion : Disposable diaper has influences in the toddler readiness to start toilet training. It has no influences in the toileting skill of toddler, method of toilet training by the parent, and the parents and environment readiness to start toilet training.